Плівки CdS на поруватих підкладках Si, одержані методом хімічного поверхневого осадження - Дяденчук, Альона Федорівна; Дяденчук, Алена Федоровна; Diadenchuk, Alona; Кідалов, В. В. (My University, 2018)
UK: У роботі одержано плівки CdS на поруватих напівпровідникових підкладках Si технологією хімічного поверхневого осадження. Вивчено морфологію та хімічний склад отриманих структур. Розглянуто можливість застосування гетероструктур CdS/porous-Si/p-Si як фотоелектричних перетворювачів сонячної енергії. RU: В работе получены пленки CdS на пористых полупроводниковых подложках Si путем химического поверхностного осаждения. Изучено морфологию и химический состав полученных структур. Рассмотрена возможность применения гетероструктур CdS/porous-Si/p-Si в качестве фотоэлектрических преобразователей солнечной энергии. EN: The purpose of this work is to develop a technology for the production of CdS films by chemical surface deposition on porous substrates of nanocrystalline silicon. The possibility of using the heterostructure CdS/porousSi/p-Si as photovoltaic solar energy converters is considered. The formation of layers CdS was carried out by the method of precipitation in a chemical bath from an aqueous solution. As a template, plates of porous silicon (Si) are used. Nanoporous silicon was obtained by electrochemical etching of single-crystal plates Si (100) of p-type conductivity with a specific impedance of 6 mΩ•cm. For the chemical surface deposition of CdS films, a freshly prepared 0.015 M aqueous solution of cadmium chloride CdCl2, 1.5 M solution of thiourea CH4N2S, and 14.28 M solution of ammonium hydroxide NH4OH were used. The process of heating the plates lasted 5 min. The final temperature was 80 °C. The morphology of the porous silicon surface, the cross-section of the resulting CdS/porous-Si/p-Si structures and the chemical composition of the films obtained were investigated using a scanning electron microscope. The chemical composition of the film surface was determined using X-ray spectral microanalysis. According to the results of the conducted studies, it has been found that the thickness of the CdS layer is homogeneous and is 10–30 microns. CdS films have n-type conductivity. X-ray diffractograms of the sample exhibit pronounced peaks at 2θ ≈ 26.5° and at 2θ ≈ 43.3°, which correspond to the hexagonal modification of CdS. There are also intense peaks from the silicon substrate. A solar photocell is produced, which is a heterostructure of n-CdS/porous-Si/p-Si. The value of the efficiency of the received solar cells exceeds 5.4 % of the efficiency value for similar structures of CdS/p-Si under the same conditions for obtaining a conductive film of n-type CdS. Thus, the heterostructures CdS/porous-Si/p-Si produced by the precipitation of CdS layers in a chemical bath from an aqueous solution can be used as the basis of photovoltaic converters for solar energy.
Пленки CdS на пористой подложке Si, полученные методом химического поверхностного осаждения
CdS films on the porous substruction of Si obtained by chemical surface deposition
Keywords: плівки CdS; поруваті підкладки Si; хімічне поверхневе осадження; фотоелектричні перетворювачі; пленки CdS; пористые подложки Si; химическое поверхностное осаждение; фотоэлектрические преобразователи; CdS films; Si porous substrate; chemical surface deposition; photovoltaic converters